2021
DOI: 10.1002/jcpy.1223
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Picky Shoppers: Who They Are and How to Spot Them

Abstract: Although pickiness fundamentally concerns one's preferences, there is currently no definition of this construct in the consumer psychology literature. This paper presents a conceptualization of shopper "pickiness"-an overly narrow latitude of acceptance around an idiosyncratic ideal point. Pickiness is revealed in two ways: pickiness by acceptance (PBA) (i.e., choosing to accept few options) and pickiness by rejection (PBR) (i.e., choosing to reject many options). This work introduces the Picky Shopper Scale t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Scales can measure any of several specific entities (i.e., independent variables, moderators, mediators, and outcome variables), some that are more enduring (typically "trait" measures) and some that are more transitory (typically "state" and/or "response" measures). Trait scales measure an enduring characteristic of a consumer [e.g., consumers who tend to be picky shoppers (Cheng et al, 2021), tend to be environmentally conscientious (Haws et al, 2014), or prefer local food (Reich et al, 2018)]. Measurement of individual differences most typically serves the role of independent variables or moderators.…”
Section: Consi De R At Ions For Va LI Dat Ed a N D I M Prov I Sed Sca...mentioning
confidence: 99%
“…Scales can measure any of several specific entities (i.e., independent variables, moderators, mediators, and outcome variables), some that are more enduring (typically "trait" measures) and some that are more transitory (typically "state" and/or "response" measures). Trait scales measure an enduring characteristic of a consumer [e.g., consumers who tend to be picky shoppers (Cheng et al, 2021), tend to be environmentally conscientious (Haws et al, 2014), or prefer local food (Reich et al, 2018)]. Measurement of individual differences most typically serves the role of independent variables or moderators.…”
Section: Consi De R At Ions For Va LI Dat Ed a N D I M Prov I Sed Sca...mentioning
confidence: 99%
“…Research that also seeks to combine psychological variables with innovation adoption theories to better explain the MFS phenomenon will lead to new insights and will contribute to theory building. For example, the recently developed picky shopper scale (Cheng et al. , 2021) differentiates between picky by acceptance and picky by rejection .…”
Section: Limitations and Future Research Agendamentioning
confidence: 99%
“…Research that also seeks to combine psychological variables with innovation adoption theories to better explain the MFS phenomenon will lead to new insights and will contribute to theory building. For example, the recently developed picky shopper scale (Cheng et al, 2021) differentiates between picky by acceptance and picky by rejection. Future research can integrate the picky shopper scale into studies comparing the shopping behaviours and innovation adoption of generation X, generation Y and the millennials using MFSs as a context.…”
Section: Advances In Mfssmentioning
confidence: 99%
“…In addition, gift decisions can be demanding due to the difficulty in gauging recipients' preferences. This is especially true for gift decisions for picky individuals, whose narrow and idiosyncratic preferences make satisfaction with gifts seem unlikely (Cheng, Baumgartner, et al, 2021). A survey revealed that 39% of Black Friday shoppers considered their recipients picky, highlighting the frequent need to buy gifts for such individuals (Cheng, Meloy, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%